Dexrazoxane efficacy for anthracycline extravasation: use in UK clinical practice. Issue 3 (15th February 2013) - Muthuramalingam, S.; Gale, J.; Bradbury, J.
Summary Extravasation is recognised as a major complication of administering intravenous chemotherapy treatment. Of the agents involved in extravasation, anthracyclines are associated with the greatest risk to patients because they are vesicant agents, having the potential to cause blistering and ulceration. If not identified and left untreated, anthracycline extravasation can lead to more serious complications such as tissue necrosis and functional impairment. Dexrazoxane (Savene®) is the only licensed antidote for the treatment of anthracycline extravasation and clinical evidence has shown Savene® to be highly effective for preventing the need for surgery following anthracycline extravasation, allowing full recovery in the majority of patients. To date, there have been eight published studies reporting a total of 102 cases of Savene® use. Here, we review the published data on the efficacy of Savene® and present an analysis of 12 UK case studies. All UK oncology centres where Savene® has been used to manage anthracycline extravasation were contacted by SpePharm UK, who requested case studies for this publication. All of the cases received, including two from our own experience of using Savene® have been included in the analysis.